Thermal degradation kinetics of sawdust under intermediate heating rates - Jaroenkhasemmeesuk C. (2017)
© 2016 Elsevier Ltd. All rights reserved. In this work, thermal degradation behavior of sawdust under N 2 and O 2 environments were investigated to derive the kinetics parameters. Thermogravimetric analysis was carried out at various intermediate heating rates (140-200 °C/min). Kinetic parameters were calculated using Kissinger-Akahira-Sunose and Flynn-Wall-Ozawa models. It was found that the activation energy of both pyrolysis and oxycombustion were different from previous studies. Higher heating rate affected not only the temperature at maximum weight loss, but also the apparent activation energy in any conversions of biomass due to pyrolysis and oxycombustion. Activation energy of sawdust pyrolysis appeared to peak around 40-50% conversions while oxycombustion did around 15-25%. The activation energy was found to be in the range between 35-110 kJ/mol and 35-129 kJ/mol for pyrolysis and oxycombustion, respectively.